Basic development projects of educational activities of universities - Логинов, Олег Владимирович (Technology audit and production reserves, 2013)
The article studies the control of projects of the development of educational activities of universities. To identify the major projects in this area, we used the approach of organization of educational services of universities by analogy with commercial enterprises. The article introduces the concept "educational product" of universities, which is defined as a combination of "specialty - specialization - level of education - form of learning." The introduction of this concept allowed forming a system of educational services, which focuses on the marketing idea of universities. We developed the structure of a set of educational services of a university as a business portfolio, strategic business units and product portfolio. Such approach provides the possibility of adaptation of the classical tools and theoretical principles of strategic management and marketing to the activities of universities. The formed system helped to identify the essence of the basic strategies of universities development and to establish the key projects of the progress of educational activities of universities, which is the foundation of the project approach to the development of the educational activities of universities.